Spinal anaesthesia for brachytherapy for carcinoma of the cervix a comparison of two dose regimes of hypebaric bupivacaine - Haus, Nikolas Jason (University of Cape Town, 2015)
Includes abstract. === Includes bibliographical references. === The main purpose of the study was to help establish the best dose regimen of hyperbaric bupivacaine, when combined with intrathecal fentanyl, for spinal anaesthesia for brachytherapy for carcinoma of the cervix. This procedure is performed as a day case at Groote Schuur Hospital.